Supporting breastfeeding In Local Communities (SILC) in Victoria, Australia: a cluster randomised controlled trial. Issue 2 (1st February 2016) - McLachlan, Helen L; Forster, Della A; Amir, Lisa H; Cullinane, Meabh; Shafiei, Touran; Watson, Lyndsey F; Ridgway, Lael; Cramer, Rhian L; Small, Rhonda
Abstract : Objectives: Breastfeeding has significant health benefits for mothers and infants. Despite recommendations from the WHO, by 6 months of age 40% of Australian infants are receiving no breast milk. Increased early postpartum breastfeeding support may improve breastfeeding maintenance. 2 community-based interventions to increase breastfeeding duration in local government areas (LGAs) in Victoria, Australia, were implemented and evaluated. Design: 3-arm cluster randomised trial. Setting: LGAs in Victoria, Australia. Participants: LGAs across Victoria with breastfeeding initiation rates below the state average and > 450 births/year were eligible for inclusion. The LGA was the unit of randomisation, and maternal and child health centres in the LGAs comprised the clusters. Interventions: Early home-based breastfeeding support by a maternal and child health nurse (home visit, HV) with or without access to a community-based breastfeeding drop-in centre (HV+drop-in). Main outcome measures: The proportion of infants receiving 'any' breast milk at 3, 4 and 6 months (women's self-report). Findings: 4 LGAs were randomised to the comparison arm and provided usual care (n=41 clusters; n=2414 women); 3 to HV (n=32 clusters; n=2281 women); and 3 to HV+drop-in (n=26 clusters; 2344 women). There was no difference in breastfeeding at 4 months in either HV (adjusted OR 1.04; 95% CI 0.84 to 1.29) or HV+drop-in (adjusted OR 0.92; 95% CI 0.78 to 1.08) compared with the comparison arm, no difference at 3 or 6 months, nor in any LGA in breastfeeding before and after the intervention. Some issues were experienced with intervention protocol fidelity. Conclusions: Early home-based and community-based support proved difficult to implement. Interventions to increase breastfeeding in complex community settings require sufficient time and partnership building for successful implementation. We cannot conclude that additional community-based support is ineffective in improving breastfeeding maintenance given the level of adherence to the planned protocol. Trial registration number: ACTRN12611000898954; Results.